Evaluation of Biomaterial Substitution in Metallurgical Coke - Armstrong, Nancy (My University, 2021)
Carbon is a necessary reductant in steel production to convert iron ore to metallic iron. The use of coal and coke causes CO2 emissions to be released into the environment. Using bio-based carbon sources has the potential to offset these emissions and reduce cokemaking overall carbon footprint. The use of biomaterial in coal blends reduces the fossil fuel requirements but to what capacity and type of biocarbon can replace coal is unknown. The full effects of coal and coke characterization from the addition of biomaterial are unknown. In this work, raw biomaterials available to industrial users were evaluated for substitution at low amounts in operational coal blends. Physically, the optical properties of carbon coke forms can provide insight into the strength, reactivity, and performance in the blast furnace, resulting from coal rank and type. The interaction of the biomaterial substitutions with coal during the coking process is evaluated to better understand the reduction in coke strength after reaction (CSR). For this purpose, a series of the pilot oven and sole heated oven tests were performed. When coal was substituted with low amounts of raw biomaterials, the most notable changes in coke texture analysis were to incipient and circular textures. In this work, data from a series of pilot oven and sole heated oven tests showed that fine coke textures and overall inerts increased. The changes in coke textures can be linked to decreases in coke strength after reaction (CSR).
THE EVALUATION OF BIOMATERIAL IMPACT ON METALLURGICAL COKE STRUCTURE FOR SUBSTITUTION OF COAL IN OPERATIONAL COAL BLENDS
Keywords: Biomaterial Coal Blend